Comparison and assessment of a different steel materials based on core losses reduction for three-phase induction motor - Yaser Atta Yassin; Ali Nasser Hussain; Nagham Yassin Ahmed (Institute of Advanced Engineering and Science, 2021)
This paper presents a core losses and performance calculation with different type of steel materials in the core design for three-phase induction motor by using